Indonesia’s Criminal Law Policy On The Victim Of Narcotics Abuse In The Perspective Of Victimology - Ariyanti, Vivi (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2018)
The design constructed by the formulation in the Law No. 35 of 2009 concerning Narcotics is that addicts and victims of narcotics abuse are given punitive measures (i.e. medical rehabilitation and social rehabilitation), whereas non-addicted narcotics abuse is given a criminal penalty. Parameters of narcotic abuse victims in the Law No. 35 of 2009 are very restricted and they are difficult to prove. Therefore, in addition to using the law, law enforcement officials also use other rules to determine the parameters of victims of drug abuse. The Law No. 35/2009, and also the law enforcement officers, uses the positivist victimology paradigm that places narcotics abusers as both perpetrators of crimes and victims of their own actions (self-victimizing victims). Meanwhile, according to radical victimology paradigm, narcotics abusers belong to precipitative victims. Based on that, this study recommend that the law formulation need to be made on the definition of drug abuse victims with the concept of depenalization, i.e. future criminal law policy includes narcotics abusers into victims who are required to undergo medical and social rehabilitation.